Empirická kritika marxismu - Pospíšil, Leopold (Lidé města, 2007)
Just like Marx and Durkheim were undeniably men of genius of their time, it is clear that Marxists and Durkheimists of the twenties century were not. The later ones are rather the most conservative and most dogmatic reactionaries in history of modern science. Despite all the rich facts gathered by exact study of past and contemporary societies proving the opposite, Marxists have elevated the old Marx’s theories to an absolute and infallible thesis of faith. As a mockery to all the gathered facts and realities, they transformed Marx’s philosophy to a religion. It is unbelievable that somebody might think that Carl Marx, being a genius and trying to be objective, might, if he lived today, dogmatically declare the obsolete and outdated theories of the last century to be still valid. Marx was an independent thinker while today’s Marxists are academic henchmen. Because I have always admired revolutionaries of our thinking, like Copernicus, Galileo Galilei, Montesquieu, Einstein, Darwin, Durkheim, and Marx, I cannot be a Marxist, an ideal slave, that is an antitheses of Marx. While the world attains new understanding of natural and social realities, followers of the 19th century philosophies are becoming “revolutionaries of yesteryears”.